Factors which are predictive of return work after stroke - M. V. Ntsiea; H. van Aswegen; S. Olorunju (AOSIS, 2013)
Stroke impacts on a survivor's ability to participate in community activities such as return to work (RTW) and affects people who are within the working age. There is a dearth of literature on RTW after stroke in developing countries. This study aimed to bridge this gap in South Africa, and was conducted within the Gauteng province as it comprises the largest share of the South African population. Seventy-two stroke survivors participated in this cross-sectional study. A demographic questionnaire; Barthel index; Modified Rivermead mobility index and Montreal cognitive assessment were used to determine the characteristics of study participants. The mean (standard deviation) scores for the Barthel Index (BI), Modified Rivermead mobility index (MRMI) and Montreal cognitive assessment (MoCA) were 19.6 (±0.2), 39.5 (±0.9) and 25.1 (±4.8) respectively. Thirty-one (43%) of the stroke survivors returned to work at six months after stroke. Stroke survivors with left hemiplegia had a greater chance of RTW than those with right hemiplegia (odds ratio 7.7). For every unit increase in the BI and MoCA score, the likelihood of RTW increased by 1.6 and 1.3 respectively. Conclusion: Side of hemiplegia, independence in activities of daily living and cognitive ability were found to be predictors of RTW at six months after stroke. It is important to identify people with cognitive impairments after stroke so that efforts can be made to increase awareness of the potential role that cognitive impairments may play in RTW.